2019
DOI: 10.1021/acs.orglett.8b04084
|View full text |Cite
|
Sign up to set email alerts
|

Extending the Substrate Scope in the Hydrogenation of Unfunctionalized Tetrasubstituted Olefins with Ir-P Stereogenic Aminophosphine–Oxazoline Catalysts

Abstract: Air-stable and readily available Ir-catalyst precursors modified with MaxPHOX-type ligands have been successfully applied in the challenging asymmetric hydrogenation of tetrasubstituted olefins under mild reaction conditions. Gratifyingly, these catalyst precursors are able to efficiently hydrogenate not only a range of indene derivatives (ee's up to 96%) but also 1,2-dihydronapthalene derivatives and acyclic olefins (ee's up to 99%), which both constitute the most challenging substrates for this transformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 25 publications
(15 reference statements)
0
14
0
Order By: Relevance
“…During the last decade our group has developed several modular P‐stereogenic chiral ligands that have proven to be excellent precursors of chiral catalysts. Although our iridium‐P,N MaxPHOX family of catalysts ( 6 ) have been successfully applied to the asymmetric hydrogenation of cyclic enamides, aryl and alkyl imines, and minimally functionalized olefins, including 2‐aryl N ‐allyl phthalimides, we found that in this particular case, using 3 a as model substrate, [((4 S ,5 S )‐Cy 2 ‐Ubaphox)Ir(COD)]BAr F 4 ( 7 ) gave the best results.…”
Section: Resultsmentioning
confidence: 94%
“…During the last decade our group has developed several modular P‐stereogenic chiral ligands that have proven to be excellent precursors of chiral catalysts. Although our iridium‐P,N MaxPHOX family of catalysts ( 6 ) have been successfully applied to the asymmetric hydrogenation of cyclic enamides, aryl and alkyl imines, and minimally functionalized olefins, including 2‐aryl N ‐allyl phthalimides, we found that in this particular case, using 3 a as model substrate, [((4 S ,5 S )‐Cy 2 ‐Ubaphox)Ir(COD)]BAr F 4 ( 7 ) gave the best results.…”
Section: Resultsmentioning
confidence: 94%
“…For this family of substrates, catalyst 32b emerged as the most suitable. 45 However, when moving to acyclic olefins, 31b gave the best enantioselectivities (Figure 7). It is remarkable that the distinct diastereomers in the ligand library gave such a diversity of results.…”
Section: Catalysismentioning
confidence: 99%
“…To demonstrate that, we moved to perform the asymmetric hydrogenation of the homoallylic alcohols 3,w hich are considered minimally functionalized olefins. [29] During the last decade our group has developed several modular P-stereogenic chiral ligands [30] that have proven to be excellent precursors of chiral catalysts.Although our iridium-P, NM axPHOX [31] family of catalysts (6)h ave been successfully applied to the asymmetric hydrogenation of cyclic enamides, [31a] aryl and alkyl imines, [32] and minimally functionalized olefins, [33] including 2-aryl N-allyl phthalimides, [34] we found that in this particular case,u sing 3a as model substrate,[((4S,5S)-Cy 2 -Ubaphox)Ir(COD)]BAr F 4 (7) [35] gave the best results.…”
Section: Angewandte Chemiementioning
confidence: 99%